The use of video assistant referee (VAR) technology in football match management - Ali, Muhsen; Khadem, Abdulrazaq (Journal of Physical Education, 2020)
The video assistant referee technology (VAR) is one of the most important modern electronic technologies used in the management of football matches at the international level, which has been adopted internationally in the most important world championships. The aim of the research is to identify cases of using video assistive judgment technology in the Spanish League and for the teams that won the first three places for the season (2019-2020). The researcher used the descriptive approach. The research sample was the Spanish League matches for the season (2019-2020) (Real Madrid, Barcelona, and Atletico Madrid). The researchers concluded that the assistive video referee technology has a great impact in determining the results of matches in a fair manner and without relying on the assessment of the personal situation by the referee, and that all teams benefit from the assistive video referee technology and that no differentiation occurs between teams because of its use. And the introduction of video assistant refereeing technology in the Iraqi league will have a positive impact on the accuracy of arbitration decisions